Digital Digital Gold Pricing M echanisms in DANA within Maqasid al-Sharī‘ah and Consumer Protection Framework: A Normative Legal Analysis - Sahira , Madhia Ramma; Robbani , Shofa; Anang , Arif Al (Universitas Islam Negeri Alauddin Makassar, 2026)
The rapid growth of application-based digital gold services has expanded public access to gold investment but also raised legal concerns over pricing transparency. Previous research largely examines the legality of digital gold trading and price fluctuations, yet pays little attention to physical gold minting costs that are revealed only at later transaction stages, despite their direct impact on consumers’ interests. This study analyzes DANA’s digital gold pricing through an integrated lens of Maqāṣid al-Sharī‘ah and Indonesian consumer protection law using normative legal methods based on statutory analysis, academic literature, and DANA’s official user terms. Findings show that delayed disclosure of minting costs creates information asymmetry and potential economic harm to consumers. From a Maqāṣid al-Sharī‘ah perspective, such opacity may constitute gharar and weaken contractual clarity. The study highlights the need for transparent, upfront cost disclosure as an integral part of fair digital gold pricing. Strengthening transparency mechanisms will not only uphold Sharī‘ah compliance and consumer rights but also guide policymakers in enhancing fintech regulation for equitable market practices.